The Role of a Dipeptide Outer‐Coordination Sphere on H2‐Production Catalysts: Influence on Catalytic Rates and Electron Transfer. Issue 6 (11th December 2012) - Reback, Matthew L.; Ginovska‐Pangovska, Bojana; Ho, Ming‐Hsun; Jain, Avijita; Squier, Thomas C.; Raugei, Simone; Roberts, John A. S.; Shaw, Wendy J.
Abstract The outer‐coordination sphere of enzymes acts to fine‐tune the active site reactivity and control catalytic rates, suggesting that incorporation of analogous structural elements into molecular catalysts may be necessary to achieve rates comparable to those observed in enzyme systems at low overpotentials. In this work, we evaluate the effect of an amino acid and dipeptide outer‐coordination sphere on [Ni(PPh2NPh‐R2)2]2+ hydrogen production catalysts. A series of 12 new complexes containing non‐natural amino acids or dipeptides was prepared to test the effects of positioning, size, polarity and aromaticity on catalytic activity. The non‐natural amino acid was either 3‐(meta‐ or para‐aminophenyl)propionic acid terminated as an acid, an ester or an amide. Dipeptides consisted of one of the non‐natural amino acids coupled to one of four amino acid esters: alanine, serine, phenylalanine or tyrosine. All of the catalysts are active for hydrogen production, with rates averaging ∼1000 s−1, 40 % faster than the unmodified catalyst. Structure and polarity of the aliphatic or aromatic side chains of the C‐terminal peptide do not strongly influence rates. However, the presence of an amide bond increases rates, suggesting a role for the amide in assisting catalysis. Overpotentials were lower with substituents at the N‐phenyl meta position. This is consistent with slower electron transfer in the less compact, para‐substituted complexes, as shown in digital simulations of catalyst cyclic voltammograms and computational modeling of the complexes. Combining the current results with insights from previous results, we propose a mechanism for the role of the amino acid and dipeptide based outer‐coordination sphere in molecular hydrogen production catalysts.